Dinosaur explorers. #8, Lord of the skies - Redcode (Comic writer); Albbie (Comic writer) (Papercutz, 2021)
The Dinosaur Explorers, Sean, Stone, and Rain, continue their explorations in the late Cretaceous period and encounter pterosaurs. The group must find a way to escape these winged predators.